Off-pump versus on-pump coronary artery bypass grafting in patients with left main disease: a randomized controlled trial - Karim Mohamed Mady; Amr Ahmed Abdou Ettish; Wael Mohamed Elfeky; Mohamed Mostafa Abdelaal (Journal of the Pakistan Medical Association, 2023)
Objective: To compare the outcome of off-pump and on-pump coronary artery bypass graft surgery in patients with left main coronary artery disease. Method: The randomised, controlled, prospective, multicentric study was conducted in 2020 during the period from January 2020 to December 2020 at Kafrelsheikh University Hospital, International Cardiac Centre and Alexandria New Medical Centre, Egypt, and comprised patients with left main coronary artery disease who underwent coronary artery bypass graft surgery. The patients were randomised to on-pump surgery group I (Control Group) and off-pump surgery group II(Interventional Group). All patients were assessed pre-operatively for the presence of comorbid conditions and post-operatively for myocardial infarction, acute kidney injury, pneumonia, sternal dehiscence and 3-month mortality. Data was analysed using SPSS 20. Results: Of the 60 patients, 44(73.3%) were men and 16(26.6%) were women. The overall mean age was 66.4±9.2 years. There were 30(50%) patients in each of the two groups. There were 2(6.7%) cases of myocardial infarction in group I and 1(3.3%) in group II. There was 1(3.3%) case of acute kidney injury in group I and none in group II. There were 3(10%) cases of pneumonia in group 1 compared to 1(3.3%) in group II. There was 1(3.3%) case of sternal dehiscence in group I and none in group II. Mortality at 3 months was 2(6.7%) in group I and 1(3.3%) in group II. There was no significant difference with respect to outcome between the groups (p>0.05). Conclusion: Off-pump coronary artery bypass graft surgery was found to be efficient and non-inferior to on-pump procedure in patients with left main coronary artery disease. Keywords: Coronary artery, Bypass, Myocardial infarction, Kidney, Diabetes, Myocardium, Pneumonia